2006
DOI: 10.1203/01.pdr.0000246480.13170.c0
|View full text |Cite
|
Sign up to set email alerts
|

Attenuated Cyclooxygenase-2 Expression Contributes to Patent Ductus Arteriosus in Preterm Mice

Abstract: Patent ductus arteriosus (DA) is the second most common congenital heart defect, the incidence of which is increased in premature infants, although mechanisms responsible are not clear. Our previous studies with genetic or pharmacological inactivation of cyclooxygenase-2 (COX-2) in mice, emphasized the importance of this enzyme in normal DA closure. The current study was designed to determine whether reduced COX-2 expression contributes to patent DA in preterm mice. Real-time PCR analysis indicated that COX-2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 23 publications
1
17
0
Order By: Relevance
“…These findings led the authors to suggest that opening of this vessel during the embryonic period is mediated by the PGE 2 -EP 4 signaling and that in its absence, the compensatory dilatory mechanism is mobilized, and this mechanism continues to maintain the vessel open after the birth, resulting in a paradoxical patent ductus arteriosus in the EP 4 -deficient mice. However, in contrast to this general idea on the patent ductus arteriosus phenotype of EP 4 (Ϫ/Ϫ) mice, Trivedi et al (2006) suggested an alternative possibility that the PGE 2 -EP 4 signaling functions close, not open, the ductus. Their suggestion was based on their findings that COX-2 is induced in the ductus around term; that the loss of COX-2 or long-term treatment with COX inhibitors leads to its opening, not closure; and that the COX-2 expression in the ductus around term was attenuated in EP 4 -deficient mice.…”
Section: Distribution and Biological Functionsmentioning
confidence: 73%
“…These findings led the authors to suggest that opening of this vessel during the embryonic period is mediated by the PGE 2 -EP 4 signaling and that in its absence, the compensatory dilatory mechanism is mobilized, and this mechanism continues to maintain the vessel open after the birth, resulting in a paradoxical patent ductus arteriosus in the EP 4 -deficient mice. However, in contrast to this general idea on the patent ductus arteriosus phenotype of EP 4 (Ϫ/Ϫ) mice, Trivedi et al (2006) suggested an alternative possibility that the PGE 2 -EP 4 signaling functions close, not open, the ductus. Their suggestion was based on their findings that COX-2 is induced in the ductus around term; that the loss of COX-2 or long-term treatment with COX inhibitors leads to its opening, not closure; and that the COX-2 expression in the ductus around term was attenuated in EP 4 -deficient mice.…”
Section: Distribution and Biological Functionsmentioning
confidence: 73%
“…Interestingly, there is also interplay between EP4 receptor activation and COX2 expression. The experiments of Trivedi et al [64] indicate that the genetic deficiency of EP4 results in attenuated COX2 expression.…”
Section: Gene-targeted Micementioning
confidence: 99%
“…When looking at the COX-deleted mice in detail, COX2 seems to be more important for DA closure than COX1. Trivedi et al [64] were the first to emphasize that COX2 has a vital role for ductal closure after term birth and is attenuated in preterm gestation. In addition to the COX2 effect, a gene dosage-dependent effect of COX1 has been documented [61,65] .…”
Section: Gene-targeted Micementioning
confidence: 99%
“…Although it is not apparent from the www.intechopen.com literature why COX deletion causes PDA in mice, we assume that the same mechanism should work as described below in mice harboring deletion of the EP4 gene, a predominant PGE 2 receptor in the DA. Trivedi et al have demonstrated that COX2 expression is attenuated in EP4-deleted mice (Trivedi,. 2006), suggesting the existence of a positive feedback loop in COX-PGE 2 cascades.…”
Section: Cyclooxygenase (Cox): the Generator Of Pgementioning
confidence: 99%